The Relationship of God Image to Level of Object Relations Development - Brokaw, Beth Fletcher (Journal of psychology and theology, 1994)
This study empirically tested the relationship of God image to level of object relations development in a Christian sample. Ninety-two undergraduate students from a religiously homogeneous population were tested with three measures of God image and three measures of object relations development. It was hypothesized that level of object relations development would show a significant positive correlation with images of God as loving and benevolent and a significant negative correlation with images of God as wrathful, controlling, and irrelevant. Scores on each of the God image instruments were correlated with scores on each of the measures of object relations development. The objective measure of object relations, the Ego Function Assessment Questionnaire-Revised (EFAQ-R), correlated significantly with all three measures of God image in the directions hypothesized. The two projective measures of object relations, the Rorschach and the Comprehensive Object Relations Profile (CORP), showed only a few significant correlations with God image scales. The strongest finding of this study was the consistent, positive correlation of multiple measures of loving God images with level of object relations development on the EFAQ-R.